2017
DOI: 10.1080/2000656x.2016.1254646
|View full text |Cite
|
Sign up to set email alerts
|

Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 2. Surgical results

Abstract: ISRCTN29932826.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 12 publications
0
81
0
1
Order By: Relevance
“…In addition, all participants had velar closure around 4 months of age according to the same surgical protocol that was performed by one of two surgeons (Rautio et al . ). This means that the reported differences in speech outcomes between groups can most probably not be explained by a difference in hearing between the two groups, but it may likely influence speech outcomes in some individuals.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, all participants had velar closure around 4 months of age according to the same surgical protocol that was performed by one of two surgeons (Rautio et al . ). This means that the reported differences in speech outcomes between groups can most probably not be explained by a difference in hearing between the two groups, but it may likely influence speech outcomes in some individuals.…”
Section: Discussionmentioning
confidence: 97%
“…The surgeons had experience with a similar procedure before initiation of the trial, and the same surgical procedures were used in both arms as only the timing of hard palate repair differed (Rautio et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Patients were then randomized for hard palate closure at 12 (EHPC) or 36 months (DHPC). Inclusion criteria, randomization method and trial design have been reported by Semb and co‐authors, and the surgical technique described in detail by Rautio et al Surgery was performed by two senior high‐volume surgeons (more than 50 cleft newborns' primary surgeries/year), calibrated according the Scandcleft protocol.…”
Section: Methodsmentioning
confidence: 99%